1974
DOI: 10.1172/jci107888
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects on Renin Release of Beta Adrenergic Antagonists with Differing Properties

Abstract: A B S T R A C T Continuous 6-h infusions of the beta adrenergic blockers dl-propranolol or oxprenolol significantly reduced plasma renin activity (PRA) and mean blood pressure in the resting rabbit and prevented the stimulatory effects of isoproterenol on renin release and heart rate. These actions were due to blockade of beta receptors, for the inactive isomer, d-propranolol, had no effect. Despite sustained high plasma concentrations of dl-propranolol (0.2 Ag/ml) in the unstimulated animal, PRA did not fall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
3

Year Published

1976
1976
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 34 publications
4
29
0
3
Order By: Relevance
“…On the other hand predominant 813-adrenoceptor blocking agents such as atenolol (Amery et al, 1976) and metoprolol (Lijnen et al, 1979) are able to inhibit the renin secretion. However, selective ,82-adrenoceptor blockers, have been shown to antagonize the secretion of renin provoked by isoprenaline and to be more powerful than non-selective and selective j1-adrenoceptor blockers in these experimental models (Weber et al, 1974;Imbs et al, 1977). The latter results together with the findings of the present study could indicate that ,81-adrenoceptors are either not at all or only to a minor extent involved in the modulation of the secretion of renin.…”
Section: Discussionsupporting
confidence: 50%
“…On the other hand predominant 813-adrenoceptor blocking agents such as atenolol (Amery et al, 1976) and metoprolol (Lijnen et al, 1979) are able to inhibit the renin secretion. However, selective ,82-adrenoceptor blockers, have been shown to antagonize the secretion of renin provoked by isoprenaline and to be more powerful than non-selective and selective j1-adrenoceptor blockers in these experimental models (Weber et al, 1974;Imbs et al, 1977). The latter results together with the findings of the present study could indicate that ,81-adrenoceptors are either not at all or only to a minor extent involved in the modulation of the secretion of renin.…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, the infusion of the beta agonist, isoproterenol, may not be comparable to any beta adrenergic properties of renal nerve stimulation. Lastly, previous studies claiming to support the existence of an intrarenal beta adrenergic receptor influencing renin release have not considered the membrane stabilizing (anesthetic) property of d,l-propranolol (20,21). The present experimental protocol was designed to avoid these above objections.…”
Section: Resultsmentioning
confidence: 99%
“…If this were the case, then the inhibitory effect of dl-propranolol on renin release might have resulted from the effects of the drug on renal hemodynamics or sodium excretion. Moreover, the d-isomer of propranolol, which is devoid of beta adrenergic inhibitory properties, is a potent membrane stabilizer (20,21). The possibility exists, therefore, that this property of dl-propranolol accounted for its ability to impair renin release.…”
Section: Introductionmentioning
confidence: 99%
“…In other experiments stimulation of the renal nerves at a rate which caused almost identical changes in renal blood flow (Coote etal., 1972;Johns & Singer, 1974a) resulted in renin release, almost all of which could be blocked by propranolol. Thus, in the study of Weber et al (1974) blockade of these indirect actions of isoprenaline by the P2-adrenoceptor antagonists could well have accounted for their greater effectiveness in blocking renin release and therefore led to the suggestion of P2-adrenoceptors mediating renin release.…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by an in vitro study (Johns, Richards & Singer, 1975) which showed that both selective and non-selective 3-adrenoceptor agonists could stimulate renin release from cat isolated renal cortical cells. In another study Weber, Stokes & Gain (1974) (1978) and Desaulles, Meisch & Schwartz (1978) concluded that, in rats Pl-adrenoceptors were involved in sympathetically-mediated renin release from the kidney. Similarly, studies both in conscious dogs (Himori, Izumi & Ishimori, 1980) and in anaesthetized dogs (Kopp, Aurell, Nilsson & Ablad, 1980) demonstrated that adrenergic renin release was probably mediated by Pl-adrenoceptors.…”
Section: Introductionmentioning
confidence: 99%